2014
DOI: 10.1111/jog.12594
|View full text |Cite
|
Sign up to set email alerts
|

Trachelectomy during pregnancy: What has experience taught us?

Abstract: The treatment of early stage cervical malignancy in a pregnant patient remains a challenge. We report the successful application of a vaginal radical trachelectomy (VRT) during pregnancy to treat a patient diagnosed with early stage cervical cancer and subsequently review the published work. A 22-year-old female diagnosed at the gestational age of 17 weeks with International Federation of Gynecology and Obstetrics stage IB1 squamous cell cervical carcinoma was treated with VRT at 19(+5) weeks. At 36 weeks, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…From an oncological point of view, a systematic review totaling more than 600 cases confirmed an overall recurrence rate < 5% and a death rate < 3%, demonstrating the safety of this approach for small invasive cervical tumors [55]. RT in pregnancy has been investigated by many teams, as first-line therapy for patients diagnosed with tumors <2 cm (≤IB1 according to FIGO 2018) [33,[56][57][58][59][60][61][62][63][64][65][66] or, in rarer situations, for patients diagnosed with tumors >2 cm (≥IB2 according to FIGO 2018) [67][68][69][70][71][72][73][74][75]. RT can be performed either through abdominal [58][59][60]63,66,67,69,72,74,76] or vaginal approach (Dargent's method) [56,57,61,71,73,75,77,78], each technique being associated with its own advantages and drawbacks.…”
Section: Surgery Conization and Trachelectomymentioning
confidence: 97%
See 2 more Smart Citations
“…From an oncological point of view, a systematic review totaling more than 600 cases confirmed an overall recurrence rate < 5% and a death rate < 3%, demonstrating the safety of this approach for small invasive cervical tumors [55]. RT in pregnancy has been investigated by many teams, as first-line therapy for patients diagnosed with tumors <2 cm (≤IB1 according to FIGO 2018) [33,[56][57][58][59][60][61][62][63][64][65][66] or, in rarer situations, for patients diagnosed with tumors >2 cm (≥IB2 according to FIGO 2018) [67][68][69][70][71][72][73][74][75]. RT can be performed either through abdominal [58][59][60]63,66,67,69,72,74,76] or vaginal approach (Dargent's method) [56,57,61,71,73,75,77,78], each technique being associated with its own advantages and drawbacks.…”
Section: Surgery Conization and Trachelectomymentioning
confidence: 97%
“…RT in pregnancy has been investigated by many teams, as first-line therapy for patients diagnosed with tumors <2 cm (≤IB1 according to FIGO 2018) [33,[56][57][58][59][60][61][62][63][64][65][66] or, in rarer situations, for patients diagnosed with tumors >2 cm (≥IB2 according to FIGO 2018) [67][68][69][70][71][72][73][74][75]. RT can be performed either through abdominal [58][59][60]63,66,67,69,72,74,76] or vaginal approach (Dargent's method) [56,57,61,71,73,75,77,78], each technique being associated with its own advantages and drawbacks. Vaginal approach allows for less manipulation of the pregnant uterus and thus may carry a lower risk of spontaneous abortion.…”
Section: Surgery Conization and Trachelectomymentioning
confidence: 99%
See 1 more Smart Citation